A periodized winter training block enhances anaerobic capacity in elite female rowers during 30-second maximal rowing - Liu, Xiaofang; Ding, Yuquan; Gong, Zhigang; Guo, Pengcheng (Frontiers in Physiology, 2026)
ObjectiveIn competitive rowing, the winter training phase is a conventional periodized block focused on foundational physiological development through land-based strength and power training. The primary aim of this phase is to enhance athletes’ force-generating capabilities and metabolic resilience. This study investigated the effects of such a 16-week periodized winter training block on anaerobic capacity and energy expenditure during a 30-s all-out rowing test in elite female rowers.MethodsFive elite female rowers (age: 20.0 ± 2.5 years; BMI: 20.8 ± 0.3 kg/m2; training experience: 4.8 ± 1.6 years) underwent pre- and post-training assessments. The winter training program consisted of three sequential phases focusing on aerobic endurance, anaerobic threshold, and race-pace intervals, with 5-6 sessions per week. Testing was conducted on the same day in the following order: (1) a 30-s all-out rowing test to assess anaerobic power output and metabolism; and (2) an incremental rowing test to exhaustion performed after a 10-min recovery, to establish individual oxygen uptake-power relationships for the maximal accumulated oxygen deficit (MAOD) method and to confirm maximal oxygen uptake (VO2max).ResultsFollowing winter training, significant improvements were observed during the 30-s all-out rowing test in mean power output (+14.1%), anaerobic energy contribution (+22.0%), and total energy expenditure (+12.1%), alongside a reduction in aerobic contribution (−16.9%) and oxygen uptake (p < 0.05). Peak post-test blood lactate concentration also increased significantly (p < 0.05). No changes were detected in body mass or energy utilization efficiency (p > 0.05). The incremental test confirmed that V̇O2max was maintained post-training (p > 0.05), ensuring that the calculated MAOD reflected true anaerobic adaptations.ConclusionWinter training markedly enhanced anaerobic capacity in elite female rowers, facilitated by a pronounced metabolic shift toward anaerobic pathways. Despite increased total energy expenditure, energy efficiency remained unchanged, suggesting improvements were driven primarily by physiological rather than technical adaptations. These findings underscore the importance of anaerobic development in competitive rowing performance.